HUBUNGAN FUNGSI KOGNITIF DENGAN KEMANDIRIAN LANSIA DALAM ACTIVITY DAILY LIVING DI UPT PELAYANAN SOSIAL LANJUT USIA BINJAI PROVINSI SUMATERA UTARA TAHUN 2021 - Lindawati Farida Tampubolon; Mardiati Br Barus; Angenia Itoniat Zega (STIKes Santa Elisabeth Medan, 2021)
Introduction: Elderly is someone who has reached the age of 60 years and over. The age of a person who is getting older will experience a decline due to the aging process, such as deterioration of the function of body cells so that it can affect changes in appearance, physical changes, decreased cognitive function, changes in the five senses such as vision, hearing, feelings, and motor changes. The problem of changes in body function can result in decreased cognitive function being the biggest cause of the inability for the elderly to carry out normal daily activities, and dependence on taking care of themselves. Goals: The purpose of this study was to determine the relationship between cognitive function and the independence of the elderly in Daily Living Activity at the UPT Social Services for the Elderly of Binjai, North Sumatra Province in 2021. Method: This study was a correlation study with a cross sectional design. Sampling was done by simple random sampling technique with a population of 176 people using the formula vincent gaspersz with a total sample of 62 respondents. Result: The statistical test results obtained p-value 0.000 (P<0,05), which indicates a relationship between cognitive function and the independence of the elderly in daily living activities at the Binjai Elderly Social Service Unit, North Sumatra Province in 2021. Conclusion: This research is expected to be an alternative for health workers in the Binjai nursing home to increase promotional efforts and preventive against problems related to handling dependence of the elderly in daily activities by means of health workers playing an active role in improving cognitive function of the elderly so that they are able to care for themselves for their survival.